IDENTIFIKASI KONDISI DAN POTENSI SUMUR BERDASARKAN DATA PTS SUMUR X - Anugrah Rachmarifqi; Sugiatmo Kasmungin; Bambang Kustono (President University, 2017)
Wells X has decreased the pressure inside the well. The thing that needs to be done on the well to determine the cause of the pressure drop is by doing Pressure, Temperature, Spinner Survey (PTS Survey) test when the well is flowing (PTS flowing) and when the well is closed (PTS shut-in). PTS flowing is done with the aim of determining the depth and contribution of feedzone, as well as determining the potential of generating electricity wells. PTS shut-in is done to determine the outflow phenomenon and determine the conditions in the wellbore. Data obtained by PTS survey are pressure, temperature, spinner speed, and cable speed. Data acquired by the PTS tool during PTS flowing and then processed, obtained that well X has three feedzone zones, ie feedzone 1 at 1084-1164 mKU depth, feedzone 2 at depth 1168-1392 mKU, and feedzone 3 at 1532 depth -1564 mKU. The contribution given by each feedzone was 6.2 kg / s at feedzone 1, 2 kg / s at feedzone 2, and 1.9 kg / s in feedzone 3. With a total mass of 10.1 kg / s of steam and power plant of 8 ton / hr / mw, well X has an energy potential of 4.55 MWe.Keywords: Pressure Temperature Spinner, Feedzone Contribution, Superheat, Condition of Wells, Reservoir Conditions